200 anos em um país distante e desigual - Luís Balkar Sá Peixoto Pinheiro (Muiraquitã, 2022)
The article reviews the Brazilian historiographical debate related to the subject of the Independence of Brazil within the scope of Grão-Pará, highlighting the limits of approaches based on the idea of the passivity of the process and the “adhesion” of that region to the Empire of Brazil. Handling official records of the time, consular, literary and journalistic sources, in addition to a wide range of historical studies produced both in the context of the Amazon and in other regions of Brazil, the analysis adopted moves towards the record of the process of Brazilian political emancipation in the “Provinces of the North” as disastrous and violent, generating repression and resentment in the region that, even at that time, translated a form of unequal and hierarchical relationship between nation and region that, lasting in time, assimilated the Amazon through the bias of subalternity, as if it were a conquered region, in a poorly disguised internal colonialism that must be denounced and broken.